East London - Huntington, F. C. (Quarterly Journal of Economics, 1889)
Journal Article East London Get access F. C. Huntington F. C. Huntington Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 4, Issue 1, October 1889, Pages 83–96, https://doi.org/10.2307/1883004 Published: 01 October 1889